2016
DOI: 10.1073/pnas.1614826113
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected central role of the androgen receptor in the spontaneous regeneration of myelin

Abstract: Lost myelin can be replaced after injury or during demyelinating diseases in a regenerative process called remyelination. In the central nervous system (CNS), the myelin sheaths, which protect axons and allow the fast propagation of electrical impulses, are produced by oligodendrocytes. The abundance and widespread distribution of oligodendrocyte progenitors (OPs) within the adult CNS account for this remarkable regenerative potential. Here, we report a key role for the male gonad, testosterone, and androgen r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 61 publications
5
81
1
Order By: Relevance
“…Using a lysolecithin model, investigators found that testosterone and androgen receptors are required for spontaneous remyelination. 22 …”
Section: Biological Actions Relevant To Msmentioning
confidence: 99%
“…Using a lysolecithin model, investigators found that testosterone and androgen receptors are required for spontaneous remyelination. 22 …”
Section: Biological Actions Relevant To Msmentioning
confidence: 99%
“…Furthermore, the Kawato research group reported that gonadal hormones, including estradiol, testosterone, and DHT, are produced at hippocampal lesions and act as modulators of synaptic plasticity (Ish et al ., ; Kawato, ). Additionally, testosterone might also be involved in spontaneous myelin regeneration (Bielecki et al ., ). One clinical study suggested that the level of testosterone was important for physical and cognitive rehabilitation (Rosario et al ., ).…”
Section: Androgen Hormone‐related Neuroplasticitymentioning
confidence: 97%
“…Indeed, testosterone treatment can prevent and even reverse neurodegeneration associated with MS . Testosterone has been found to promote myelin formation and regeneration . Testosterone treatment of MS patients has been found to significantly suppress PBMC production of IL‐2 while increasing TGFbeta1 production .…”
Section: Elucidation Of the Role Of Oxidative Stress (Os) And Mitochomentioning
confidence: 99%
“…197,198 Testosterone has been found to promote myelin formation and regeneration. [199][200][201][202] Testosterone treatment of MS patients has been found to significantly suppress PBMC production of IL-2 while increasing TGFbeta1 production. 203 In addition, evidence indicates that estrogen, progesterone, and testosterone treatment improve cognitive functions in MS patients.…”
Section: Hormonesmentioning
confidence: 99%